Efetividade da participação no legislativo capixaba : um estudo sobre as audiências públicas do orçamento (2007-2014) - Zorzal, Gabriela (2015)
This research is a study about Annual Budget Law (Lei Orçamentaria Anual - LOA) of public hearings performed by Assembleia Legislativa do Espirito Santo (ALES) from 2007 until 2014. The main purpose of this work is the effectiveness of public hearings participation, anchored in two dimensions: the deliberative moment and the hearings results. We assume that, despite the difficulty of measuring practical effects, Participatory Institutions such as the LOA public hearings, act in a way of intensifying democracy, specially in the allocation of resources according to social will. In this perspective, this research analyzes public hearings components (legislators profile, institucional design, participants profile, government influence and parliamentarian amendments) to evaluate the participation effectiveness. For this analysis, we used multi method approach combining three research tools: document analysis (LOA reports, laws and public hearings videos), survey (surveys applied to people in public hearings of 2014) and semistructured interview (with Finance Committee parliamentarians). Our analysis points to public hearings low effectiveness as result of the combination of several factors, including low institutionalization, Government influence in the process because of the relationship with the parliamentarians and using parliamentarian amendments as an electoral strategy.